Co-Benefits of Disaster Risk Management - Vorhies, Francis; Wilkinson, Emily (World Bank, Washington, DC, 2016)
Many ex ante measures taken to reduce disaster risk can deliver co-benefits that are not dependent on disasters occurring. In fact, building resilience to climate extremes and disasters can achieve multiple objectives. These are secondary to the main objective of disaster risk management of avoiding disaster losses, but identifying and measuring additional co-benefits can enhance the attractiveness of disaster risk management investments. Co-benefits are often economic, such as investment in dams or irrigation to reduce drought risk generating greater productivity; but they can also include significant environmental and social benefits. This paper identifies some of the potential categories of co-benefits associated with disaster risk management investments, expanding on typologies created by agencies seeking to promote social and environmental safeguarding in their work. The paper looks at previous studies on disaster risk management where co-benefits are mentioned but not explored in any detail. The paper examines two new case studies where environmental and socioeconomic co-benefits were uncovered in an irrigation project to reduce drought risk, and an urban flood risk management project, in Jamaica and Mexico, respectively. This review points to several challenges in traditional cost-benefit analysis techniques and puts forward alternative approaches to identify environmental and socioeconomic co-benefits when planning disaster risk management investments. The authors argue that a comprehensive disaster risk management co-benefits framework is needed that includes and categorizes all potential positive environmental and socioeconomic impacts. Co-benefits research focused on revisiting existing cases and developing new case studies could play an important role in this regard.